2018
DOI: 10.1113/jp275371
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional modulation of glutamatergic synaptic transmission by metabotropic glutamate type 7 receptors at Schaffer collateral–CA1 hippocampal synapses

Abstract: Neurotransmitter release is driven by Ca influx at synaptic boutons that acts on synaptic vesicles ready to undergo exocytosis. Neurotransmitter release is inhibited when metabotropic glutamate type 7 (mGlu ) receptors provoke a reduction in Ca influx, although the reduced release from synapses lacking this receptor suggests that they may also prime synaptic vesicles for release. These mGlu receptors activate phospholipase C (PLC) and generate inositol trisphosphate, which in turn releases Ca from intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…The priming activity of Munc13 (Ma et al, 2011) plays a key role in SV docking through assembly of the Munc13-Rim1-Rab3 complex (Dulubova et al, 2005) and SNARE complex. Munc13-1 forms supramolecular self-assemblies that serve as independent release sites (Sakamoto et al, 2018) through which phospholipase C (PLC)-coupled receptors (Bauer et al, 2007;Martín et al, 2010) enhance the RRP size (Martín et al, 2018). b ARs and Epac also activate PLC, translocate Munc13-1, enhance Rab3A-RIM1a interaction, and increase SV docking (Ferrero et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The priming activity of Munc13 (Ma et al, 2011) plays a key role in SV docking through assembly of the Munc13-Rim1-Rab3 complex (Dulubova et al, 2005) and SNARE complex. Munc13-1 forms supramolecular self-assemblies that serve as independent release sites (Sakamoto et al, 2018) through which phospholipase C (PLC)-coupled receptors (Bauer et al, 2007;Martín et al, 2010) enhance the RRP size (Martín et al, 2018). b ARs and Epac also activate PLC, translocate Munc13-1, enhance Rab3A-RIM1a interaction, and increase SV docking (Ferrero et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While further studies will be needed to explain the current discrepancy between genetic and pharmacological approaches, these data indicate that mGlu 7 regulates high-frequency transmission at SC-CA1 synapses. Recently, Martín et al (2018) demonstrated that prolonged activation of mGlu 7 leads to potentiation of excitatory post-synaptic currents recorded by pyramidal cells in CA1. This potentiation of neurotransmitter release is dependent on PLC and the vesicle release proteins Munc13-2 and Rim1α.…”
Section: Mglu 7 In Synaptic Transmission and Plastmentioning
confidence: 99%
“…mGlu7 has been shown to inhibit neurotransmitter release upon the activation of G i/o and the subsequent inhibition of calcium channels 33 , 34 . However, recent evidence has suggested that the prolonged activation of mGlu7 facilitates glutamate release via a G i/o -independent pathway through the translocation of Munc13 to the particulate fraction 35 , 36 . The deneddylated mGlu7 mislocalized from the active zone may no longer regulate synaptic vesicle release, thereby reducing the release probability.…”
Section: Discussionmentioning
confidence: 99%